IMMU-44. INHIBITING IMMUNOSUPPRESSIVE IDO1 IN ADULTS WITH MALIGNANT GLIOMA – A MOVING TARGET THAT CHANGES WITH TREATMENT, CELL OF ORIGIN, AND AGING. (11th November 2019) - Ladomersky, Erik; Zhai, Lijie; Lauing, Kristen; Qian, Jun; Bell, April; Otto-Meyer, Sebastian; Dussold, Corey; Lukas, Rimas; Wainwright, Derek
Abstract: We previously demonstrated that glioblastoma (GBM) cell IDO1 increases intratumoral immunosuppressive regulatory T cells (Tregs; CD4+CD25+FoxP3+) and decreases overall survival (OS) in the syngeneic GL261 model. IDO1 is characterized as an enzyme that converts the amino acid, tryptophan, into kynurenine. With the finding that IDO1 expression by GBM cells promotes intratumoral Treg accumulation, it was surprising to find that this process was unaffected by the pharmacological treatment with an IDO1 enzyme inhibitor (IDO1i). This led us to question the optimal therapeutic strategy for leveraging an IDO1i against GBM. Utilizing simultaneous whole brain radiation (RT), anti-PD-1 mAb, and an IDO1i, we discovered a long-term survival advantage in 40% of young WT mice engrafted with either GL261 or CT-2A (n=9–10/group; p< 0.01). Unexpectedly, dual treatment with RT and anti-PD-1 achieved a similar long-term survival advantage in IDO1KO-, but not in WT mice with GBM (n=14/group; p< 0.01), confirming that the therapeutic target of IDO1i was in non-GBM cells. Notably, the triple immunotherapeutic treatment was less effective in elderly mice analogous to the median age of a GBM patient diagnosis (n=20–22/group; p< 0.01) and coincident with increased IDO1 expression in the elderly human brain (n=1, 152; p< 0.01). Our working hypothesis is: (i) advanced aging increases IDO1 levels in the brain; (ii) RT elicits the release of GBM cell neoantigens; (iii) IDO1+ lymph node (LN) DCs process/present GBM cell neoantigens to cognate CD8+ T cells; (iv) IDO1i treatment decreases the suppression of IDO1+ DC:CD8+ T cell priming; (v) anti-PD1 treatment enhances LN priming initialized by RT + IDO1i; (vi) brain-resident IDO1+ DCs accumulate during advanced aging and suppress the newly-generated brain-infiltrating CD8+ GBM-specific T cells independent of IDO1i. Our work highlights the immunosuppressive role of advanced aging and the need to better understand gero-neuro-immuno-oncology interactions for enhancing future immunotherapeutic efficacy in adults with GBM.